Development of business communications of enterprises in the conditions of change (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. Transformational changes in the economy require new scientific approaches to ensure the competitiveness of enterprises. One of the important aspects and factors of influence is business communications, which are realized in interpersonal relations, information exchange and management decision-making processes.Goal is a theoretical justification for the development of business communications in a changing environment.Methods. The article uses a monographic method, analysis, method of generalization of scientific approaches.Results. The article identifies scientific approaches to the essence of the concept of "communication", their characteristics, objectives and principles. The structuring of communication by socio-economic and technological components is substantiated. The purposes of internal communication at the enterprises in the conditions of changes are defined. There are two components of communication: socio-economic and technological. The author's interpretation of business communication in the conditions of changes as a set of measures, which provides for the formation and implementation of management decisions to create, develop the enterprise, maintain its reputation to meet consumer needs, organize decent work and pay, increase competitiveness. The tasks of business communications which will promote their further development at the enterprises in the conditions of changes are generalized.The principles of construction of effective communications at the enterprises in the conditions of changes are defined: the principle of the scientific approach; the principle of terminological certainty; unity of rational and emotional in human behavior; the principle of situationality; the principle of striving to increase the level of objectivity; the principle of humanism; the principle of development, or ontogenesis, of the subjects of communication; the principle of systematization of the subjects of communications; the principle of the probability of undiagnosed, hidden factors; the principle of incomplete adequacy of any complexity of behavior models of subjects; the principle of infinity of the process of cognition; principle of support of law; the principle of necessity and possibility of communication management.Conclusions. The conducted research allows to generalize scientific approaches to business communications at the enterprises in the conditions of changes and to define directions of scientific search concerning their development.